Building successful partnerships between teaching assistants and teachers: Which interpersonal factors matter?. (January 2022) - Jardí, Andrea; Webster, Rob; Petreñas, Cristina; Puigdellívol, Ignasi
Abstract: This article identifies the factors that characterise effective interpersonal partnerships between teaching assistants (TAs) and teachers working in inclusive schools in Catalonia (Spain). This phenomenological study, based on 40 semi-structured interviews with 22 TAs and 18 teachers revealed that the main interpersonal factors affecting partnerships were: feeling at ease; trust; respect; and valuing one another. Participants detailed key aspects such as personal affinity, professional compatibility, open communication, a sense of belonging to a class-group, and teamwork, as additionally important for successful partnerships. The findings provide insight into how schools can support the development of effective TA-teacher partnerships. Implications are discussed. Highlights: Achieving effective TA-teacher partnerships is a complex process that requires time, effort, and external support. Interpersonal factors that affect TA-teacher partnerships should be considered when analysing their impact. Personal affinity, open communication, the sense of belonging, and professional compatibility are key to feel at ease. Trust can be achieved when partners' expectations are fulfilled, with open communication and teamwork. The role attributed and the interpersonal treatment are essential to feel respected and valued.